Out-of-pocket payments and loss of income among long-term breast cancer survivors in Germany: a multi-regional population-based study - Schneider, Jana; Hernández, Diego; Schlander, Michael; Arndt, Volker; Bertram, Heike; Brenner, Hermann; Eberle, Andrea; Holleczek, Bernd; Koch, Lena; Nennecke, Alice L.; Pritzkuleit, Ron; Waldmann, Annika; et al. (Journal of cancer survivorship, 2023)
This study aims to examine the magnitude of out of pocket (OOP) payments and income loss, as well as to identify socioeconomic and clinical factors among long-term breast cancer (BC) survivors in Germany.